2011
DOI: 10.1007/s12206-011-0709-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular simulation study on adhesions and deformations for Polymethyl Methacrylate (PMMA) resist in nanoimprint lithography

Abstract: The NIL (nanoimprint lithography) process is explored through numerical simulation, utilizing MD (molecular dynamics), with a focus on the resin deformations and the adhesion between the resin material and the tool. For the force-field of the Polymethyl Methacrylate (PMMA), used for the resin material, a united atom model is employed. For temperature control in the MD simulation, the recursive multiple chains of the Nosé-Poincaré thermostat is applied. The deformation and adhesion in the NIL process are explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The MD simulation of the all-atom model used the consistent valence force field (CVFF) to obtain the potential parameters for the intermolecular and intramolecular interactions [21,34,36]. The non-bonded interaction energy at the PP-mold insert interface directly determined the adhesion force, which was one of the important factors affecting the demolding quality.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MD simulation of the all-atom model used the consistent valence force field (CVFF) to obtain the potential parameters for the intermolecular and intramolecular interactions [21,34,36]. The non-bonded interaction energy at the PP-mold insert interface directly determined the adhesion force, which was one of the important factors affecting the demolding quality.…”
Section: Methodsmentioning
confidence: 99%
“…At present, the MD method has been widely applied to most of the research areas, such as the nanoimprint lithography technology [21,22,23], the micro-injection molding technology [24,25,26], the direct injection joining technology [27,28], the calculation of interfacial adhesion [29,30], and the simulation of self-assembled monolayer [31]. For the study of polymer molding, the MD method was mainly used by researchers to analyze the influences of nanostructure shapes [22,23,27,32], the mold insert and polymer materials [30,33], the anti-stick treatment of surface [32,34], the processing parameters [26,32], and other factors on the molding qualities. However, the above studies mainly focus on the nanoimprint lithography technology, and there are few reports on the micro-injection molding.…”
Section: Introductionmentioning
confidence: 99%
“…These results provided a basis for studying the physical and chemical changes of SAMs surface with low surface energy. Kwon et al [21] studied the effect of FOTS SAMs on the imprinting quality by molecular dynamics method. The self-assembled alkanethiols is also an alternative in anti-adhesion application, since the alkanethiol monolayers could be effectively adsorbed on metal surface.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the surface coating improved the molding quality of microstructures in replication fidelity, aspect ratio and surface roughness. Kwon et al [ 17 ] studied the effect of thickness of self-assembled FOTS coating on the imprinting quality by a molecular dynamics method. The self-assembled alkanethiols is also an alternative in anti-adhesion application, since the alkanethiol monolayers can be effectively adsorbed on the metal surface.…”
Section: Introductionmentioning
confidence: 99%